LEGITIMATION OF RELIGIOUS MUSIC OF SABYAN GAMBUS’ SONG “DEEN ASSALAM” AS A PERCEPTIVE RESPON TO ISLAMIC RADICALIZATION IN INDONESIA - Umilia Rokhani (Institut Seni Indonesia Yogyakarta, 2019)
Islam is often referred as being a radical movement or activity. Sabyan Gambus, through their song cover, responses to the situation in their song “Deen Assalam”. This song was created as an effort to minimize and reduce the society’s misthinking on the concept and implementation of Islamic teaching. Thus, a study of values implied in the song becomes essential to view such a perception shift within the society as a legitimation upon the work as well as the positioning of Islam in the structural world of Indonesian people. An analysis of the song lyrics is, accordingly, essentially needed.The theory of Riffaterre is applied to study the song lyric. Meanwhile, a theory of Bourdieu is employed to review the legitimation achievement of the work production practices. The behaviorism method is used in analyzing the agents’ behaviors during the production process to reach a legitimation that can be considered as shifting of position and perception of the society.The legitimation of Sabyan Gambus’ works by analyzing the response from the society can be considered as some possibilities of the emergence of a more moderate Islam in Indonesia. The analysis of internal meaning may also create some possibilities to audience to gain the power of value that affects the power relation and other external factors. Therefore, both internal and external work analyses are necessary to show the influence of work production and its legitimation achievement on its position and perception of the society.